Research on resource management and service mapping method for reconfigurable flexible network - Bao-jin WANG; Bin-qiang WANG; Zhi-ming WANG (Tongxin xuebao)
Reconfigurable flexible network (RFNet) based on resource re-composition was proposed.The network service in RFNet was composed of special components,and could construct the new network service to satisfy a coming traffic demand by component composition technology in both software and hardware area.After introducing the architecture of RFNet,a process flow mechanism of resource management,carraying network mapping and network service mapping was proposed.By simulation evaluation,the mechanism was confirmed to provide the support of heterogeneous networks construction and coexistence,and especially the reconfigurable service carrying network mapping(RSCNM)algorithm based on load balance had an advantage over network successful construction ratio(SCR),maximum node stress,average link utilization rate and average revenue.